The Application of Online Caricature Momentcam as A Media for Biography Text Writing About Jokowi’s Outstanding Character By Senior High School Students - Susi Darihastining; Puji Rahayu Ningsih; Aang Fatihul Islam; Titik Indarti (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This research aims at examining the application of online caricature application MomentCam on student’s biography text writing about Jokowi’s outstanding characters. This research employed a qualitative method. The data in this research was in the form of students’ writing results from the application of MomentCam. The subject of this research was a tenth grade students of senior high school. The research particularly aims at identifying (1) students’ biography writing skills outcomes that explain positive and outstanding characters of Jokowi by using MomentCam online caricature application and (2) the description of positive and outstanding characters of Jokowi within students’ biography text writing by using MomentCam online caricature applicationThis research confirms that the utilization of MomentCam online caricature application is successful in assisting students’ writing ability, particularly in writing biography text which consisted outstanding characteristics of Jokowi.